Pengaruh pH dan Temperatur pada Ekstraksi Antioksidan dan Zat Warna Buah Stroberi - H. Maria Inggrid; Albertus Reynaldi Iskandar (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Indonesia is one of the tropical country that is potential to cultivate different types of plants, include strawberry. The use of synthetic dyes in foods are harmful to body health. Therefore, natural dyes can be used as alternative substitutes that can reduce harmful effects to the body. Dyeing capability of strawberry is caused by anthocyanin that gives red color. Furthermore, strawberry contains antioxidant that prevents free radicals in the human tissue. The purpose of this experiment is to study the effect of pH and temperature in the extraction of anthocyanin from strawberry towards total content of anthocyanin, antioxidant activity and total content of phenolic compound. The strawberry were extracted at the temperature variation of 5oC, 30oC and 60oC, and pH variation of 2, 7 and 12 respectively using water as solvent. The highest total anthocyanin content in the strawberry is 44.4mg/100grsample that obtained at 5oC and pH of 2. The highest antioxidant activity and total phenolic content in the strawberry are 91.2% and 218.7 ppm respectively.